2012
DOI: 10.2139/ssrn.2549463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Existential Issues Training on Marital Communication Among Iranian Women

Abstract: Marital communication is acknowledged as a crucial indicator of matrimonial quality, and has undergone studies in recent times with respect to its determinants. While existing literature has focused on the value of existential issues from four existential counseling theories in improving matrimonial quality, there is a dearth of experimental research to substantiate the effects of the existential issues on marital communication. This study aims to fill the gap and highlight the potential of the existential iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In tandem to that, Group Cognitive Behavior Therapy that infused Quranic Therapy reduced parenting stress and increase marital adjustment (AlHorany, et al, 2011). We also found that another psychological treatment, Existential issues Training that integrates Quranic Therapy reduces existential anxiety of multiple roles responsibilities in women and improve marital communication and satisfaction (Kalantarkousheh et al, 2012). Effectiveness of our Marital Islamic Psycho-spiritual Intervention has also been documented (Ahmad & Hassan, 2013) to increase spiritual and marital wellbeing.…”
Section: Problem Statementmentioning
confidence: 56%
“…In tandem to that, Group Cognitive Behavior Therapy that infused Quranic Therapy reduced parenting stress and increase marital adjustment (AlHorany, et al, 2011). We also found that another psychological treatment, Existential issues Training that integrates Quranic Therapy reduces existential anxiety of multiple roles responsibilities in women and improve marital communication and satisfaction (Kalantarkousheh et al, 2012). Effectiveness of our Marital Islamic Psycho-spiritual Intervention has also been documented (Ahmad & Hassan, 2013) to increase spiritual and marital wellbeing.…”
Section: Problem Statementmentioning
confidence: 56%
“…The sub category which emerges as we focus on the broad theme of marital delay is causes of marital delay [21][22][23][24][25]. As is evident from a look on the national statistical data on the age at marriage, the youth willfully delay marriage.…”
Section: Causes Of Marital Delay In Kashmirmentioning
confidence: 99%